From risk to enjoyable, safe swallowing: Current studies on the development of aerated food, liquid, and semi-gel structures for dysphagia management - Woroud A. Alsanei (International Journal of Food and Nutritional Health, 2026)
Dysphagia significantly affects quality of life, increasing risks of malnutrition, dehydration, aspiration pneumonia and long-term healthcare challenges. Traditional dietary interventions often modify food, liquid textures, but adherence can decline due to visually unappealing and unappetizing of dysphagia-friendly foods. Therefore, this review highlights the current trend of aerated (foamed, air bubbly) structures in food, liquid and semi-gel products designed for individuals with dysphagia to modified texture, sensory and swallowing experiences. This review summaries the incorporating air bubbles softening food texture, reducing choking hazards, and improving safety while consuming meals for dysphagic people. Additionally, air bubbles contribute to an improved sensory experience by enhancing mouthfeel, facilitating flavor release, achieving taste balance, and ensuring safety while also promoting healthier eating habits and overall well-being for individuals with dysphagia. Innovations in aerated structures play a crucial role in enhancing nutrition, improving palatability, and stimulating appetite. The implementation of such structures in products designed for individuals with dysphagia, requires collaboration among food scientists, nutrition experts, speech-language pathologists, and culinary specialists. However, there is a critical need for comprehensive clinical trials on aerated structures to understand their impact on swallowing dynamics and health outcomes, and to improve their development for enhancing safety, nutrition, and quality of life in affected populations.